La ciència en la poesia catalana del segle XIX - Vall, Xavier (Caplletra. Revista Internacional de Filologia, 2005)
The article offers a panoramic review of the relationship that Catalan poetry had with diverse sciences and technology, in the period which goes from the beginnings of Romanticism (although it still presents some illustrated reminiscences) to Realism and Naturalism. The theoretical debate is considered, as long as diverse attitudes of the writer towards science (that oscillate from mythification to the most retrograde tirades, passing through critical scientism) are pointed out. It also shows the numerous possibilities generated by the incorporation of scientific and technological elements, which so much affect stylistic and ideological aspects. The paper is based on an ample sample, which is focused on diverse authors and some motives are followed too. This sample, besides the interest that it has in itself, can also help to place in context Joaquim M. Bartrina’s poetic work, in which the relationship between Literature and Science especially bears fruit. Although the use of scientific and technological elements is neither a guarantee of modernity, progress nor of good literary results, it renews a poetry which used to be highly stereotyped, even moved away of the reality sometimes, in addition to establishing bridges between sciences and the humanities.